Comparison of feedlot and carcass characteristics of Angus, Hereford, Brahman, Charolais, and Gelbvieh crossbred steers - D.T. Hickok; R.R. Schalles; D.E. Franke; Michael E. Dikeman (Kansas Agricultural Experiment Station Research Reports, 1992)
Feedlot performance of 207 steers with various percentages of Angus, Hereford, Charolais, Brahman, and Gelbvieh breeding were compared at a constant 1) days fed, 2) adjusted carcass backfat, and 3) slaughter weight. As the percentage of Angus, Hereford, or Brahman increased, growth rate decreased, whereas increasing the percentage of Charolais increased growth rate. Increasing the percentage of Gelbvieh increased weaning weight but had little effect on post-weaning gains. Increasing percentage of Charolais increased feed conversion efficiency, whereas the other breeds were similar, except that at a constant slaughter weight, greater percentage of Hereford improved feed conversion efficiency. Increasing the percentage of Charolais increased carcass weight and ribeye area and decreased yield grade, but marbling was not different from that of Angus. An increase in percentage of Hereford caused a decrease in carcass weight, ribeye area, marbling, and quality grade. Increasing percentage of Angus decreased carcass weight and ribeye area but increased marbling and quality grade. Increasing percentage of Brahman caused the greatest reduction of marbling and quality grade of any breed. Increasing the percentage Gelbvieh breeding resulted in increased ribeye area and decreased marbling at constant days fed and slaughter weight.
Keywords: Cattlemen' s Day; 1992; Kansas Agricultural Experiment Station contribution; no. 92-407-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 651; Beef; Cattle; Breeds; Performance; Carcass